Analysis of colorectal cancers in British Bangladeshi identifies early onset, frequent mucinous histotype and a high prevalence of RBFOX1 deletion. - Sengupta, N; Yau, C; Sakthianandeswaren, A; Mouradov, D; Gibbs, P; Suraweera, N; Cazier, J; Polanco-Echeverry, G; Ghosh, A; Thaha, M; Ahmed, S; Feakins, R; et al. (2013)
BACKGROUND: Prevalence of colorectal cancer (CRC) in the British Bangladeshi population (BAN) is low compared to British Caucasians (CAU). Genetic background may influence mutations and disease features. METHODS: We characterized the clinicopathological features of BAN CRCs and interrogated their genomes using mutation profiling and high-density single nucleotide polymorphism (SNP) arrays and compared findings to CAU CRCs. RESULTS: Age of onset of BAN CRC was significantly lower than for CAU patients (p=3.0 x 10-5) and this difference was not due to Lynch syndrome or the polyposis syndromes. KRAS mutations in BAN microsatellite stable (MSS) CRCs were comparatively rare (5.4%) compared to CAU MSS CRCs (25%; p=0.04), which correlates with the high percentage of mucinous histotype observed (31%) in the BAN samples. No BRAF mutations was seen in our BAN MSS CRCs (CAU CRCs, 12%; p=0.08). Array data revealed similar patterns of gains (chromosome 7 and 8q), losses (8p, 17p and 18q) and LOH (4q, 17p and 18q) in BAN and CAU CRCs. A small deletion on chromosome 16p13.2 involving the alternative splicing factor RBFOX1 only was found in significantly more BAN (50%) than CAU CRCs (15%) cases (p=0.04). Focal deletions targeting the 5' end of the gene were also identified. Novel RBFOX1 mutations were found in CRC cell lines and tumours; mRNA and protein expression was reduced in tumours. CONCLUSIONS: KRAS mutations were rare in BAN MSS CRC and a mucinous histotype common. Loss of RBFOX1 may explain the anomalous splicing activity associated with CRC.